An ontology-based approach to product extension services modelling in servitisation. (22nd November 2010) - Shen, Jin; Wang, Liya; Sun, Yiwen
Manufacturers are undergoing a transition from being product-focused to service-based. Product Extension Services (PESs) are essential ingredients in various servitisation strategies. As the business of PESs grows quickly, it is imperative to develop a formal conceptual model. Thereby, this paper investigates an ontology-based approach for representing information and semantic knowledge of intangible PESs. A general knowledge representation scheme, called PESO, is hierarchically developed. At the lower level, a meta-ontology is defined where agreed terms and vocabulary are explained explicitly. The concepts and relations in the ontology are elicited from empirical research. The process ontology in OWL-S is reused by using ontology import mechanism. A precise and formal representation based on OWL is also provided. The resulting PESO provides a common semantic foundation for meaningful representation and knowledge exchange across multi-disciplinary teams and heterogeneous systems. A specific PES called 'Building Solution' is finally illustrated to demonstrate the potential of PESO.